TENDENCIES OF DEVELOPMENT OF REGIONAL BUDGETARY SYSTEM AND THE BUDGETARY POLICY OF THE EUROPEAN UNION AT THE PRESENT STAGE - D. Bolotin (Вестник университета)
Object of research in this article is the budgetary process in the European Union and the directions of improvement of the budgetary relations at the supranational level. A research objective is assessment of the current tendencies and problems of development of the budgetary relations at the level of the European Union. Results of a research have shown that the budg-etary policy of the European Union were significantly transformed to the period of the 1960-2010 and now its non-coordination became one of barriers of economic growth of EU countries. In article the analysis of the basic principles and problems of realization of the budgetary policy at the present stage is carried out.